Evaluation of Attitude Towards Collaboration in Physicians and Nurses: A Cross-Sectional Research - Pınar Eraslan; Yildirim Beyazit Gulhan (Association of Nurse Managers, 2020)
INTRODUCTION: In this study, it was aimed to investigate the attitudes of physicians and nurses working in a aducational and research hospital towards collaboration according to socio-demographic variables. METHODS: This study was conducted in a aducational andr esearch hospital between April-May 2018. 1292 physicians and nurses constituted the universe and the sample size was 297 for this non-homogeneous universe. The questionnaires prepared in accordance with the aim of the study were completed by physicians and nurses on a voluntary basis. 'Jefferson Scale of Attitudes Toward Physician-Nurse Collaboration' was used to evaluate the collaboration score. For statistical analysis, t-test, One-way Anova test, and after the Anova test, Scheffe was used as complementary post-hoc analysis to determine the differences. The p value of <0.05 was accepted for statistical significance. RESULTS: According to the occupational variable, nurses have a more positive attitude and are more prone to collaboration than physicians. There was a statistically significant relationship between the variables of profession, gender, age, education level and nursing study area. There was no statistically significant relationship between demographic characteristics such as physician study area, experience and visit status (p>0,05). DISCUSSION AND CONCLUSION: It was concluded that the implementation of joint vocational training programs that will strengthen the collaboration attitude and the creation of an atmosphere of Professional respect will provide positive results in health service delivery.